Moderate sedation helps improve future behavior in pediatric dental patients - a prospective study - Denise Espíndola ANTUNES; Karolline Alves VIANA; Paulo Sucasas COSTA; Luciane Rezende COSTA
Abstract There is little evidence on the long-term effects of pharmacological management in children undergoing dental treatment. This study aimed to assess children's behavior in consecutive dental sessions following oral rehabilitation using different pharmacological regimens for behavioral control. Participants were preschoolers who were previously treated for caries under one of the following: no sedative, oral sedation with midazolam, oral sedation with midazolam/ketamine, or general anesthesia. The children's behavior in the follow-up sessions was assessed using the Ohio State University Behavioral Rating Scale (OSUBRS); higher scores represented less cooperative behavior (range 5-20). Follow-up assessments were conducted on 50 children under four years old for up to 29 months. Data were analyzed by the Friedman/Wilcoxon tests and Cox regression model. OSUBRS mean (standard deviation) scores for the whole sample decreased from 11.9 (5.4) before treatment to 6.8 (3.2) at the final recall session (p < 0.001). Moderate sedation with midazolam (OR 2.9, 95%CI 1.2-6.9) or midazolam/ketamine (OR 4.3, 95%CI 1.6-11.4) improved children's future behavior. The general anesthesia group (n = 4) had a small sample size and the results should be considered with caution. Although invasive dental treatment negatively affected the child's behavior in the dental chair, they became more cooperative over time. Moderately sedated children showed better prospective behavior than those in the non-sedation group.